La raison dans le mythe (ou comment les récits traditionnels accommodent les formes nouvelles de rationalités) - Bernard Mezzadri (Pallas, 2009)
The emergence of Ionian physics constitutes to my mind an epistemological break away from the previous world views. The confrontation and dialogue between those forms of thought henceforward remain an irreplaceable heuristic tool, the pertinence of which we mean to propose from two instances which illustrate, each in its own way, the aptitude of mythical narratives to make the most of notions and concepts, even of new intellectual procedures by integrating them into their narrative logic. In the first instance, we see Tiresias the theologian deal playfully with the allegories wherewith the gods and their ordeals used to be reduced to a description of the elements and natural phenomena. For the soothsayer of the Bacchae, it was Zeus who, allegorist in concreto, in order to cheat his vindictive spouse, substitutes a piece of ether for Dionysos. In the second instance, the sovereign of Olympus carries out a real scientific experiment, measuring, as an expert surveyor would do, the world which he governs but the centre of which he is ignorant of : a world which for the purpose in hand becomes as abstract as a mathematical object. Not only therefore -as had long been emphasized- the birth in Greece of a positive and critical thought did not dry up the creative mytho-poetic strain but one can note that the latter was able to take hold of the new theories and representations to feed its fabrication, thereby depriving them ipso facto of their critical potentiality.